POPULAÇÃO E FAMÍ LIA DE UMA VILA AÇORIANA: AS VELAS DA ILHA DE S. JO RGE ( 1 7 6 6 - 1 7 9 9) - Matos, P. T. de; José Damião Rodrigues; Artur Boavida Madeira (População e Sociedade, 1998)
This paper aims to characterize the demographic and social d!)namics in the Azares during the Eari!J Modem Age, [ocusing on the demographic evolution o[ the island o[ São Jorge in the second half o[ the 1 8th centur!J. To do so, we swdied densit!J, volume and r!Jthms of population growth in the parishes of Velas (5. }orge!. The paper concludes b!J anal!)sing the data in the róis de confessados e com ungados o[ the paris h, in arder to capture the household composition and so to obtain a picture of the cit!) 'S demographic S!JStem.